Whole Genome Sequencing and Progress Toward Full Inbreeding of the Mouse Collaborative Cross Population. Issue 5 (1st May 2019) - Shorter, John R; Najarian, Maya L; Bell, Timothy A; Blanchard, Matthew; Ferris, Martin T; Hock, Pablo; Kashfeen, Anwica; Kirchoff, Kathryn E; Linnertz, Colton L; Sigmon, J Sebastian; Miller, Darla R; McMillan, Leonard; et al.
Abstract: Two key features of recombinant inbred panels are well-characterized genomes and reproducibility. Here we report on the sequenced genomes of six additional Collaborative Cross (CC) strains and on inbreeding progress of 72 CC strains. We have previously reported on the sequences of 69 CC strains that were publicly available, bringing the total of CC strains with whole genome sequence up to 75. The sequencing of these six CC strains updates the efforts toward inbreeding undertaken by the UNC Systems Genetics Core. The timing reflects our competing mandates to release to the public as many CC strains as possible while achieving an acceptable level of inbreeding. The new six strains have a higher than average founder contribution from non- domesticus strains than the previously released CC strains. Five of the six strains also have high residual heterozygosity (>14%), which may be related to non- domesticus founder contributions. Finally, we report on updated estimates on residual heterozygosity across the entire CC population using a novel, simple and cost effective genotyping platform on three mice from each strain. We observe a reduction in residual heterozygosity across all previously released CC strains. We discuss the optimal use of different genetic resources available for the CC population.